Клавесин Марии-Антуанетты: роман / Наталья Александрова - Александрова Наталья Николаевна (Артефакт-детектив, 2009)
Экземпляры: ф.8 (2014) / Инвентарный номер: 56168 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44